대구 지역 고등학생의 아침식사 이용실태 및 아침식사 대용식 인식조사 - 최재혁(Jae-Hyuk Choi); 박금순(Geum-Soon Park) (東아시아食生活學會誌, 2016)
This study investigated eating behaviors of high school students (209 males and 230 females) in Daegu region by gender. As a result of analyzing breakfast intake frequency, 'Not rarely eat' showed the highest (25.1%), followed by '5 times a week' (24.4%), '2 times a week' (17.3%), '3 times a week' (15.0%), '1 time a week' (11.6%), and '4 times a week' (6.6%). Regarding reasons for skipping breakfast, 'lack of time' showed the highest percentages. For their breakfast, 53.5% of students ate boiled rice with side dishes. Regarding reasons for skipping breakfast, 'buy and eat snack' showed the highest percentages. Regarding favorite breakfast menu, 'rice roll, rice ball, rice burger' showed the highest percentage (55.4%), followed by 'bread & cereal' (28.7%) and 'fruits & vegetable' (7.7%). Regarding purchase of breakfast alternatives, 'Yes' was highest. Considering actors for choosing a breakfast alternative, there is a need for 'convenience of food consumption', 'spending less time', 'easy cooking', 'favorite menu' and 'taste' of the breakfast alternative. When asked how much they like breakfast alternative menus, they responded that they liked 'rice roll, rice ball, rice burger' (3.91), 'bread & cereal' (3.67), 'fruit & vegetable' (3.66), 'noodle' (3.39), 'porridge' (3.18) and 'rice cake' (3.07). This result shows that breakfast menus should be developed according to high school students preferences.